Efficacy of Topically Administered Rho-Kinase Inhibitor AR-12286 in Patients With Exfoliation Syndrome and Ocular Hypertension or Glaucoma - Skaat, Alon; Jasien, Jessica V; Ritch, Robert (Journal of glaucoma, 2016)
To evaluate the efficacy of rho-associated protein kinase inhibitor, AR-12286 topical solution, for its effect in eyes with exfoliation syndrome (XFS) and ocular hypertension (OHT) or exfoliative glaucoma (XFG) and examine any lasting effect on intraocular pressure (IOP) after discontinuation. Prospective, double-masked, randomized, interventional study. Patients with XFS and OHT or XFG were enrolled. The study eyes were treated once daily with AR-12286, randomized to 0.5% or 0.7% for 24 weeks. Visits included baseline, 1, 4, and 12 weeks after drug initiation; at 12 weeks AR-12286 was discontinued for 1 week and was resumed at week 13. At the week 24 visit, AR-12286 was discontinued, and a final reexamination was performed at week 25. Ten patients were treated. Mean baseline IOP was 25±2.4 mm Hg, mean IOP was reduced to 19.1±2.3 mm Hg at 1 week (P<0.001), 17.5±3.6 mm Hg at 4 weeks (P<0.001), and 17.4±3.6 mm Hg at 12 weeks (P<0.001), yielding an average IOP reduction of 23.6%, 30%, and 30.4%, respectively. At the week 13 visit, 1 week after the drug was discontinued, mean IOP increased to 21.6±5.4 mm Hg (P=0.06 compared with baseline visit). At week 24, the mean IOP was 21.8±7.8 mm Hg (P=0.2, and AR-12286 was discontinued). At week 25, the mean IOP was 21.3±5.3 mm Hg (P=0.06). AR-12286 was well tolerated and provided statistically significant reduction in IOP in patients with XFS and OHT or XFG. This drug may represent an additional therapeutic paradigm for the treatment of XFG.